Rose under fire - Wein, Elizabeth (Hyperion, 2013)
When young American pilot Rose Justice is captured by Nazis and sent to Ravensbrück, the notorious women's concentration camp, she finds hope in the impossible through the loyalty, bravery, and friendship of her fellow prisoners.